Maternal Compliance in Utilisation of Antenatal Care Services on the Incidence of Preeclampsia: Literature Review - Ratna Anjelika; Bagoes Widjanarko; Ayun Sriatmi (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: Maternal mortality rate (MMR) is an important indicator of the health and well-being of a society, and remains a serious global problem. Preeclampsia is a health problem that can occur in pregnant women who are more than 20 weeks pregnant. Preeclampsia is one of the leading causes of maternal death in Indonesia. The incidence of preeclampsia in pregnant women occurs due to not doing early detection. The importance of Antenatal Care (ANC) check-ups is recognised as a crucial preventive measure to ensure the health of mothers and babies, and to detect early complications during pregnancy. However, ANC service coverage in Indonesia is still below the national target, indicating the need to improve awareness and access to these services. Utilization of Antenatal Care (ANC) services needs to be done by pregnant women in order to detect early and carry out appropriate treatment of pregnant women's health problems, especially preeclampsia. Objective: To analyze the relationship between the compliance of pregnant women in utilizing antenatal care services and the incidence of preeclampsia. Method: This research is a literature review with a scoping review method using the PRISMA approach. The data used in this study used online database literature from Google Scholar, Science Direct, and Scopus with the last 5 years. Result: Based on several previous studies, low compliance of pregnant women in attending ANC visits can be a risk factor for preeclampsia. Pregnant women who are committed to regular check-ups during pregnancy can detect diseases and complications early, including preeclampsia. Quality and regular ANC services can detect pregnancy risks early and help prevent maternal mortality. In this study revealed that the greatest risk of preeclampsia that might occur in pregnant women who are not compliant in conducting ANC is 67 times, this is certainly very risky for the health of pregnant women and babies. Conclusion: This study cloncludes that regular Antenatal Care (ANC) visits are crucial to detect and manage complications early. The low rate of ANC visits should encourage healthcare providers to innovate in promoting ANC in an engaging and understandable way.